Cathepsin D as a Promising Target for the Discovery of Novel Anticancer Agents - Dubey, Vijaya; Luqman, Suaib (Current Cancer Drug Targets, 2017)
Background: Cathepsin D (CATD), one of the aspartyl endoproteinase involved in different physiological processes and signaling pathways, is accountable for metabolic breakdown of intracellular proteins, the activation of growth factors, hormones, and precursors of enzyme, the processing of antigens, enzyme inhibitors and activators and the regulation of apoptosis. Implication as a Target: Studies have confirmed the role and significance of CATD in an assortment of pathological conditions like Atherosclerosis, Ainactive proCATD, it undergoes diverse cleavages to attain a desired conformation in an alzheimer, Cancer, Cardiovascular, Huntington and Parkinson diseases. Amalgamated and veiled as cidic milieu to act as a functionally active protein. In search of new candidate target (s) for cancer, CATD has attracted a wide group of investigators across the globe and is being recognized as a well-defined marker in cancer especially for breast and hormone-dependent cancer. Methods: In this review, PubMed, Sci-finder and other search engines were used to gather information on Cathepsin D. The necessary and relevant information was thoroughly studied to make the article appropriate to highlight all the aspects related to Cathepsin D and its role in cancer. Findings & Conclusion: The present review illustrates structural, functional and regulatory aspects of CATD in cancer, its significant role in angiogenesis, metastasis, invasion, apoptosis, cell proliferation, and therapeutic potential besides the benefits of targeting CATD by the natural products in cancer chemoprevention.
Keywords: apoptosis